Storage Case for Special Controlled Drug - Jeebkaew, Kittiwath; Kittawan Sangwong,; Yuttapol Polhan,; Wirayut Pannakham, (Journal of Industrial Technology and Innovation, 2024)
The aim of this research is to create a storage case for special controlled drug and find out the efficiency of medicine storage boxes for special controlled drug. The researchers designed a storage case for special controlled drug using Arduino as a control. Inside the box, there is an LCD screen showing the number of pills. When taking the medicine out to use, there is a limit switch that is used to count the six doses of the medicine. Use a 220-volt electrical system. There is power from a 5,000 mAh backup battery in case of a power outage. Turning on and alerting when less than two doses are remaining will cause the LED to notify. Experiment to determine the efficiency of counting the number of doses of 6 drugs from 20 trials. It was found that there were two errors in total, which resulted in an average of 10 percent error from normal operation. Which in the test was considered to be at a good level.